Delayed coloanal anastomosis: an alternative option for restorative rectal cancer surgery after high‐dose pelvic radiotherapy for prostate cancer. (8th July 2020) - François, M.‐O.; Buscail, E.; Vendrely, V.; Célérier, B.; Assénat, V.; Moreau, J.‐B.; Rullier, E.; Denost, Q.
Abstract: Aim: Restorative total mesorectal excision (TME) for rectal cancer after high‐dose pelvic radiotherapy for prostate cancer has been reported to provide an unacceptable rate of pelvic sepsis. In a previous publication we proposed that delayed coloanal anastomosis (DCAA) should be performed in this situation. The present study aimed to assess the feasibility and outcomes of this strategy. Method: Between 2000 and 2018, 1094 men were operated on for rectal cancer in our institution. All men with T2/T3 mid and low rectal cancer with preoperative radiotherapy and restorative TME were considered for this study ( n = 416). Patients with external‐beam high‐dose radiotherapy (EBHRT) for prostate cancer (70–78 Gy) were identified and compared with patients with conventional long‐course chemoradiotherapy (CRT) followed by TME. We compared our already published historical cohort (2000–2012), including arm A (CRT + TME; n = 236) and arm B (EBHRT + TME; n = 12), with our early cohort (2013–2018), including arm C (CRT + TME; n = 158) and arm D (EBHRT + TME‐DCAA; n = 10). The end‐points were morbidity, pelvic sepsis, reoperation rate and quality of the specimen. Results: Overall morbidity was not significantly different between groups. Pelvic sepsis decreased from 50% (arm B) to 10% (arm D) with the use of DCAA ( P = 0.074), and was similar between arms A, C and D. Quality of the specimen was not significantly different between the four groups. Conclusion: Our results suggest that TME with DCAA in patients with previous EBHRT is feasible, with the same postoperative pelvic sepsis rate as conventional CRT.